Home page for accesible maths 3 Differentiation

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

3.2 Basic properties of differentiable functions

Let us start with a very basic fact that however is not immediately obvious from the definition:

Proposition 3.2.1.

If f:IR is differentiable at some x0I then f is also continuous at x0. If f is differentiable then it is continuous.

Proof.

The differentiability of f in x0 implies the convergence of the difference quotient

f(x)-f(x0)x-x0

to a number f(x0), as xx0, and hence

f(x)-f(x0)= (f(x)-f(x0)x-x0-f(x0))(x-x0)+f(x0)(x-x0)
00+f(x0)0=0 as xx0,

so f is continuous at x0 by definition of continuity. ∎

Key idea of proof.

write f(x)-f(x0) in terms of difference quotient and f(x0)

Example 3.2.2.

Example 3.1.2(1) provides an example of a differentiable function. According to Proposition 3.2.1, it is therefore continuous – a fact familiar to us from previous modules. Example 3.1.2(2) instead gives us a function which is not differentiable. However, we know from MATH113 that it is continuous. This proves that the converse of Proposition 3.2.1 is not true in general, namely:

Comment: A differentiable function is always continuous. But a continuous function need not be differentiable.

Exercise W3.3.

Construct three substantially different functions which are continuous but not differentiable. Explain but you do not have to prove all details.

Definition 3.2.3.

A local extremum of a function f:I is a point x0I such that there is δ>0 and either f(x)f(x0) at all xI(x0-δ,x0+δ) (local minimum) or f(x)f(x0) at all xI(x0-δ,x0+δ) (local maximum).

Proposition 3.2.4.

Let f:IR be a continuous function which has a local extremum at some x0I. If f is differentiable at x0 then f(x0)=0.

Proof.

Exercise A3.1. ∎

Proposition 3.2.5 (Sum, Product and Quotient Rules).

Let f,g:IR be differentiable at some x0I, and let λR. Then:

  • (i)

    f+λg is differentiable at x0 with

    (f+λg)(x0)=f(x0)+λg(x0).
  • (ii)

    fg is differentiable at x0 with

    (fg)(x0)=f(x0)g(x0)+f(x0)g(x0).
  • (iii)

    If g(x0)0 then fg is differentiable at x0 with

    (fg)(x0)=f(x0)g(x0)-f(x0)g(x0)g(x0)2.
Remark 3.2.6.

Before we can prove this, we have to recall a few simple facts from MATH113:

  • If f,g:I are continuous at some x0I then f+g and fg are continuous at x0.

  • If additionally g(x0)0 then g(x)0 for x in some neighbourhood of x0, and fg is defined in that neighbourhood and continuous at x0. More precisely, continuity of g at x0 implies that there is δ>0 such that, for xI(x0-δ,x0+δ), we have g(x)0, so on I(x0-δ,x0+δ) we can define fg and it is continuous at x0.

Proof.

(i) Exercise X (easy).

(ii) We already know that f and g are differentiable at x0, so their difference quotients at x0 converge to f(x0) and g(x0); continuity at x0 implies g(x)g(x0) and f(x)f(x0) as xx0. Combining these facts, we can calculate the difference quotient of fg:

Comment: A standard trick we have already encountered in Proposition 3.2.1: add and subtract auxiliary terms in order to split into more familiar subexpressions.

f(x)g(x)-f(x0)g(x0)x-x0= f(x)g(x)-f(x0)g(x)+f(x0)g(x)-f(x0)g(x0)x-x0
= f(x)-f(x0)x-x0g(x)+f(x0)g(x)-g(x0)x-x0
f(x0)g(x0)+f(x0)g(x0),xx0,

which completes the proof.

(iii) Since g is continuous at x0 and g(x0)0, we have that 1g is well-defined in a neighbourhood of x0 and continuous at x0; thus in particular 1g(x)1g(x0), as xx0. We can now compute the difference quotient:

f(x)/g(x)-f(x0)/g(x0)x-x0= f(x)/g(x)-f(x0)/g(x)+f(x0)/g(x)-f(x0)/g(x0)x-x0
= 1g(x)f(x)-f(x0)x-x0-f(x0)g(x)g(x0)g(x)-g(x0)x-x0
1g(x0)f(x0)-f(x0)g(x0)2g(x0),xx0,
= f(x0)g(x0)-f(x0)g(x0)g(x0)2,

which concludes the proof. ∎

Key idea of proof.

add and subtract auxiliary terms in difference quotients

Exercise L.

Study differentiability of f: defined byf(x)=xn.

Example 3.2.7.

Let us study

f:(-π/2,π/2),f(x)=tan(x)2=(sin(x)cos(x))2.

This is well-defined since cos is strictly positive on (-π/2,π/2). Moreover, sin and cos are differentiable on this domain and hence the quotient rule implies that tan is differentiable, and the product rule in turn implies that tan2 is differentiable on this domain. We can calculate it explicitly using the formulas of the product and quotient rule, namely

f(x)=2tan(x)tan(x)=2tan(x)cos(x)2+sin(x)2cos(x)2=2sin(x)cos(x)3.

In contrast, the function

g:(0,π),g(x)=(sin(x)cos(x))2

is not well-defined since cos(π/2)=0, so it does not make sense to speak about continuity or differentiability at all.

Example 3.2.8.

We would like to determine the derivative of

f:[0,)[0,),f(x)=xp/q,

with p,q, if it exists.

(1) Consider first p=1 and q arbitrary. Then we have fq(x)=x, and fq is differentiable with derivative equal 1 and constant difference quotient. The product rule then implies

1=fq(x)-fq(x0)x-x0=(fq-1(x)+fq-2(x)f(x0)++fq-1(x0))f(x)-f(x0)x-x0.

Suppose x0>0. Then f(x) and all its powers are strictly positive, so we can write

f(x)-f(x0)x-x0=1fq-1(x)+fq-2(x)f(x0)++fq-1(x0)1qfq-1(x0)=1qx0-q-1q,

as xx0. So f is differentiable on (0,) with f(x0)=1qx0-q-1q. Instead for x0=0, we find

f(x)-f(x0)x-x0=x1/qx=x-q-1q,

which converges to 1 if q=1 and diverges otherwise if q>1. Thus f is not differentiable at 0 except when q=1.

(2) Now let both p,q be arbitrary and g(x)=x1/q, so that f=gp; we know from part (1) that the function g is differentiable on (0,) for all q and at 0 if and only if q=1. Then the product rule applied p-1 times together with (1) implies that f is differentiable on (0,) with

f(x0)=(gp)(x0)=pgp-1(x0)g(x0)=px0p-1q1qx0-q-1q=pqx0p-qq=pqx0pq-1.

It can be shown to be differentiable at 0 if and only if p/q, and in that case

f(0)={1:p/q=10:p/q1.

The formula actually holds for all positive real exponents, not only the rational ones, but that is a bit more involved to show, see MATH210/215.

Theorem 3.2.9 (Chain rule).

Let I,JR be intervals, x0I, and f:IJ and g:JR functions such that f is differentiable at x0 and g is differentiable at f(x0). Then the composition gf:IR is differentiable at x0 with

(gf)(x0)=g(f(x0))f(x0).
Proof.

Exercise X. ∎

Example 3.2.10.

Consider the functions

f:,f(x)=sin(x)

and

g:,g(x)=|x|

and the point x0=0. We notice that almost all assumptions of the chain rule are fulfiled except that g is not differentiable at sin(x0)=sin(0)=0, according to Example 3.1.2(2). Thus we cannot apply the chain rule to gf. It is actually possible to show that gf is not differentiable at x0=0, in the same way as in Example 3.1.2(2): we compute the difference quotient

gf(x)-gf(x0)x-x0=|sin(x)|-|sin(x0)|x-x0={sin(x)x1:x>0-sin(x)x-1:x<0,

so

gf(x)-gf(x0)x-x0{1:x0-1:x0.

Since the left and right-sided limits do not coincide, gf is not differentiable at 0. Now let us look at a different point, say x0=2. Then f is differentiable at 2 and g is differentiable at f(2)=sin(2)>0, with (gf)(2)=g(sin(2))cos(2)=cos(2), according to the chain rule.

What about generic points? One finds that gf is differentiable at all points except at π, multiples of π.

If instead we take f(x)=sin(x)+2 then f()(0,), so gf is differentiable.

Comment: This example shows how crucial it is to verify that all assumptions of the theorem are fulfiled. Always remember the full theorem, not only the calculation formula!

Exercise W4.1.

Let α>0 be a rational number and

f:[0,),f(x)=xαsin(1x).

Determine for which α values the function f is differentiable. (Hint: split into the two cases x0=0 and x00 and use Example 3.2.8.)

Theorem 3.2.11 (Inverse function theorem).

Let f:IR be a strictly monotone continuous function, with inverse f-1:f(I)I. If f is differentiable at x0I and f(x0)0 then f-1 is differentiable at y0=f(x0) with

(f-1)(y0)=1f(x0)=1f(f-1(y0)).

In order to prove this theorem we need a general tool:

Lemma 3.2.12.

Let f:IR be a continuous function. If f is differentiable at x0I then there is a continuous function ϕ:IR such that

f(x)-f(x0)=(x-x0)ϕ(x),xI.
Proof.

Let

ϕ(x)={f(x)-f(x0)x-x0:xI,xx0f(x0):x=x0.

Then ϕ is continuous at xx0 by the quotient rule for continuity (Remark 3.2.6 above, or MATH113 for details) because numerator and denominator are continuous and the denominator is nonzero at xx0 and (*) is clearly fulfiled. Furthermore, differentiability of f at x0 implies that

f(x)-f(x0)x-x0f(x0),xx0,

thus ϕ(x)ϕ(x0) as xx0, so ϕ is continuous at x=x0 as well. Equation (*) in this case becomes 0=0 which is trivially true. ∎

Exercise W4.2.

Prove the following statement:

Let f:I be strictly monotone and continuous with x0I and write y0:=f(x0) and y=f(x). Then

yy0 if and only if xx0.
Proof of Theorem 3.2.11.

We would like to compute the difference quotient

f-1(y)-f-1(y0)y-y0

and show that it converges as yy0. Let ϕ:I be as in Lemma 3.2.12. Then ϕ(x)0 for all xI because f is strictly monotone and ϕ(x0)=f(x0)0 by assumption. Write y=f(x) so that x=f-1(y) as in Exercise W4.2. Then

f-1(y)-f-1(y0)y-y0=x-x0f(x)-f(x0)=1ϕ(x)=1ϕ(f-1(y))

which is well-defined because ϕ(x)0. From Exercise W4.2 we know that yy0 if and only if xx0. Furthermore, ϕ and f-1 are continuous, so the composition ϕf-1 is continuous as well and so ϕ(f-1(y))ϕ(f-1(y0))=f(f-1(y0))0, as yy0. This implies that

f-1(y)-f-1(y0)y-y0=1ϕ(f-1(y))1f(f-1(y0)),yy0,

which proves the theorem. ∎

Key idea of proof.

express difference quotient of f-1 as inverse of difference quotient of f

Example 3.2.13.

Consider the function

f:[-π/2,π/2],f(x)=sin(x).

Then f is continuous and strictly monotone. Notice that if we changed the domain to e.g. [0,π] then f would no longer be monotone.

Let x0[-π/2,π/2]. Then f is differentiable at x0 with f(x0)=cos(x0)0, which is nonzero if and only if x0(-π/2,π/2), so let us make this additional assumption, x0(-π/2,π/2). Then we can apply the inverse function rule to find that f-1=arcsin:[-1,1][-π/2,π/2] is differentiable at y0(-1,1) with

arcsin(y0)= (f-1)(y0)=1f(f-1(y0))=1cos(arcsin(y0))
= 11-(sin(arcsin(y0)))2=11-y02.

Consider now the case x0=π/2. Then

f-1(y)-f-1(y0)y-y0=1f(x)-f(x0)x-x0

and the denominator converges to f(x0)=cos(π/2)=0, so the fraction does not converge, so f-1 is not differentiable at x0=π/2. Analogously for x0=-π/2.